2013
DOI: 10.1007/s10661-013-3295-z
|View full text |Cite
|
Sign up to set email alerts
|

Small effects of a large sediment contamination with heavy metals on aquatic organisms in the vicinity of an abandoned lead and zinc mine

Abstract: The effects of the long-term contamination of water reservoirs with mine effluents were investigated at an abandoned mine site in Upper Silesia, southern Poland. The studies covered metal content and mobility in bottom sediments as well as water chemistry in relation to the content of metals in selected macrophytes and their physiology and the composition of phyto- and zooplankton communities. Although it is 40 years since mining ceased, reservoir sediments are still heavily contaminated with cadmium, zinc and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 77 publications
1
34
0
Order By: Relevance
“…The best physicochemical conditions for biota appeared to occur in Azure Lake, which had an acidic to neutral pH and a relatively low concentration of metals. The strongly acidic pH of the Purple and Yellow Lakes favors the occurrence of metals as free metal ions, which are more bioavailable and therefore, have a higher (Kushner 1993;Ciszewski et al 2013). Complexes of metals with strong ligands, especially sulphates, found in high concentrations in the Yellow and Purple lakes, could potentially decrease this metal toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best physicochemical conditions for biota appeared to occur in Azure Lake, which had an acidic to neutral pH and a relatively low concentration of metals. The strongly acidic pH of the Purple and Yellow Lakes favors the occurrence of metals as free metal ions, which are more bioavailable and therefore, have a higher (Kushner 1993;Ciszewski et al 2013). Complexes of metals with strong ligands, especially sulphates, found in high concentrations in the Yellow and Purple lakes, could potentially decrease this metal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…There have been relatively few studies on the organisms living in various post-mining water bodies, as these studies are difficult to conduct and require specialized techniques (Woelfl and Whitton 2000). However, researchers have begun to describe the organisms that live in these environments (Derham 2004;Geller et al 2012Geller et al , 2013Ciszewski et al 2013;Wołowski et al 2013;Sienkiewicz and Gasiorowski 2015). There is a relatively large number of reports on the subject of the species diversity and physiology of cyanobacteria and algae (DeNicola 2000;Gross 2000;Lessmann et al 2000;Steinberg et al 2012;Wołowski et al 2008Wołowski et al , 2013Lessman andwater properties on the rotifer community in three acidic pit lakes, created from abandoned pyrite opencast mines, in the Sudety Mountains in southern Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few cases exist where metals in sediments were significantly related to those aquatic insects. Because organisms accumulate in only the biologically available species of the polluting metals, there is not always a correlation between metal concentrations in sediments with those in aquatic insects from the same sampling reach [33,30]. However, Pilo et al [34] observed that a concentration gradient between metals in organisms and sediments is most often the same for all feeding guilds in rivers around the world.…”
Section: Resultsmentioning
confidence: 99%
“…These methods are connected with the phenomenon in which compound content in the determined extract increases proportionally with the extraction strength of the reagent used. When it comes to extraction of trace elements (heavy metals) the methods used most often are (arranged according to the increasing strength of extraction): nitric acid, also with hydrogen peroxide (Ciszewski et al 2013(Ciszewski et al , 2014, aqua regia (PN-ISO 11466:2002), hydrofluoric acid (Kicińska 2009(Kicińska , 2011.…”
Section: A Review Of Analytical Methods Used In the Study Of Waste Mamentioning
confidence: 99%